Фотоэлектрические преобразователи для измерения неэлектрических величин - Рожнова, Т. Г.; Кошевой, Н. Д.; Бурлеев, О. Л.; Костенко, Е. М. (ХНУРЭ, 2010)
Повышение точности, надежности и технологичности, а также уменьшение массогабаритных показателей измерительных преобразователей таких неэлектрических величин как угловые и линейные перемещения, давление, температура являются актуальными задачами. Эффективно решить их можно с привлечением волоконно-оптической техники. The problem of inreasing manufacturability and reducing mass and dimensions characteristics of photoelectric converters of angle and linear shifts is formulated. Methods of measuring the said parameters are improved which are based on placing the input butts of lightguide filaments of a fiber optic converter on a horizontal line, use of a disk with holes made on three tracks with a certain discreteness. The developed new pfotoelectric converters can find wide application in measuring angle and linear shifts, pressure, temperature and other parameters.
Keywords: фотоэлектрический преобразователь; световодные жилы